A single amino acid substitution in the transmembrane domain of glycoprotein H functionally compensates for the absence of gL in pseudorabies virus - Vallbracht, Melina; Schnellen, Marina; Seyfarth, Annemarie; Fuchs, Walter; Küchler, Richard; Mettenleiter, Thomas C.; Klupp, Barbara (Viruses, 2024)
Herpesvirus entry requires the coordinated action of at least four viral glycoproteins. Virus-specific binding to a cellular receptor triggers a membrane fusion cascade involving the conserved gH/gL complex and gB. Although gB is the genuine herpesvirus fusogen, it requires gH/gL for fusion, but how activation occurs is still unclear. To study the underlying mechanism, we used a gL-deleted pseudorabies virus (PrV) mutant characterized by its limited capability to directly infect neighboring cells that was exploited for several independent serial passages in cell culture. Unlike previous revertants that acquired mutations in the gL-binding N-terminus of gH, we obtained a variant, PrV-ΔgLPassV99, that unexpectedly contained two amino acid substitutions in the gH transmembrane domain (TMD). One of these mutations, I662S, was sufficient to compensate for gL function in virus entry and in in vitro cell-cell fusion assays in presence of wild type gB, but barely for cell-to-cell spread. Additional expression of receptor-binding PrV gD, which is dispensable for cell-cell fusion mediated by native gB, gH and gL, resulted in hyperfusion in combination with gH V99. Overall, our results uncover a yet-underestimated role of the gH TMD in fusion regulation, further shedding light on the complexity of herpesvirus fusion involving all structural domains of the conserved entry glycoproteins.
Gesehen am 18.11.2024
Erstveröffentlichung online: 22. Dezember 2023